PENGGUNAAN BAHASA INGGRIS PADA FITUR QUICK CHAT DALAM INTERAKSI PEMAIN GAME ONLINE PUBG MOBILE - Rena Juliana; Reni Juliani (SOURCE : Jurnal Ilmu Komunikasi, 2021)
PUBG Mobile has features that help in the interaction process between players such as Quick Chat, Chat and Voice Chat. Exclamatory words and sentences using English are available in the Quick chat list in the game. The purpose of this study is to find out how the use of English in the Quick Chat feature in the interaction of PUBG Mobile game players. This research is a type of literature research with a qualitative approach. The results of the study show that the use of English in the Quick Chat feature in the interaction of PUBG Mobile game players belongs to the register language variation which has a function as a command. The use of Message in the Quick Chat feature is a form of differentiating the form of communication used by PUBG Mobile game players with other online games. English used as the link players from different countries.